Keanekaragaman Jenis Bambu Di Cagar Alam Rawa Danau Serang Banten Sebagai Materi Pengembangan Pendidikan Konservasi - Leksono, Suroso Mukti; Sjaifuddin, Sjaifuddin; Marianingsih, Pipit; Rahmah, Siti Sarah Aulia; Ekanara, Bambang; Fajariyanti, Nofita (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2020)
The Rawa Danau Nature Reserve in Serang Banten is a highland swamp conservation area that is still left on the island of Java, but its existence is currently very threatened by human activities to fulfill its needs. Therefore, awareness of the importance of biodiversity through conservation education is needed. Conservation education requires materials or facilities that are close to people's lives, one example is bamboo plants. Bamboo is quite well known by the public, because it is used in everyday life. This study aims to find out the types of bamboo in Rawa Danau natural reserves which are then packaged as material for the development for Conservation Education. The research and development method is used to obtain the Conservation Education product. The result found 8 types of bamboo consisting of 5 genera, namely Dinochloa scandens, Gigantochloa apus, Gigantochloa atroviolacea, Gigantochloa pseudoarundinacea, Schizostachyum iraten, Bambusa vulgaris, Dendrocalamus asper, Gigantochloa atter. Furthermore, people’s knowledge about the types of bamboo are used as material for Conservation Education that can increase knowledge, attitudes, skills, awareness and participation of the community in preserving environmental sustainability